Radiological Evaluation of the Therapeutic Response of Malignant Diseases: Status Quo, Innovative Developments and Requirements for Radiology - Höink, A. J.; Heindel, W.; Buerke, B. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
In consequence of the rapid development of newer targeted and personalized tumor therapies, radiology as an essential component of the treatment concept of numerous malignant diseases needs to improve in order to adequately capture and evaluate the effects, but also the side effects of these novel therapeutic agents. The early recognition of therapy response or failure is crucial for the optimal planning of the further treatment and can therefore have direct impact on the chances of recovery and the survival time of oncological patients. In previous years, the goal of medical imaging was to just qualitatively assess the increase or reduction in the size of tumors and their metastases, which was often achieved by a simple subjective estimation of the tumor findings by the diagnosing radiologist. Nowadays, radiology is faced with the challenge of evaluating changes during therapy quantitatively and of visualizing therapeutic effects that are more discrete (e. g. necrosis, altered tumor perfusion). The importance of an adequate assessment of therapy response is further underlined by the fact that in these days, a good portion of oncological patients are enrolled in clinical trials, in which the quantitative radiological evaluation of malignant disorders is an important surrogate parameter. On the basis of this development, the demands for radiology to provide more sophisticated assessments of therapy response and documentation of imaging findings have been constantly growing. The following article provides an overview of the established and still widely spread but in particular also the latest imaging modalities and evaluation criteria with regard to oncological diseases as well as of the increasing demands on radiology that result from these developments. Beyond that, future advancements in tumor imaging are taken into account and the new challenges these developments will bring are discussed.Key points:• In the era of personalized medicine, evaluation criteria that are individually adapted to the respective patient are required.• Radiology needs to substantially contribute to oncological treatment concepts and the evaluation of therapeutic response.Citation Format:• Höink AJ, Heindel W, Buerke B. Radiological Evaluation of the Therapeutic Response of Malignant Diseases: Status Quo, Innovative Developments and Requirements for Radiology. Fortschr Röntgenstr 2014; 186: 927 – 936
Keywords: biological effects; PET-CT; treatment effects; MR imaging; CT; segmentation